COMPARISON OF TRADITIONAL AND MODERN CONSTRUCTION EFFICIENCY IN TRANSPORTATION INFRASTRUCTURE DEVELOPMENT PROJECTS - Hartanto, Sri; Manurung, Edison Hatoguan (International Journal of Multidisciplinary Research and Literature, 2025)
In recent decades, the development of construction technology has produced two main approaches in the implementation of transportation infrastructure projects, namely traditional and modern construction methods. The selection of an efficient construction method affects the project's duration and impacts the construction's cost, quality, and environmental impact. It aims to analyze and compare the efficiency of the implementation time of transportation infrastructure projects between traditional and modern construction methods and identify differences in the cost of implementing transportation infrastructure projects using traditional and contemporary construction methods. Evaluate the quality of construction results and the environmental impact of traditional and modern construction methods in transportation infrastructure projects. This research method is by reviewing journals, books, reports, and scientific articles related to the efficiency of traditional and modern construction, conducting case studies on transportation infrastructure development projects, both conventional and contemporary, involving experts, contractors, or project managers to gain in-depth insight into the construction efficiency of the two methods, using questionnaires to collect data from various transportation development projects, comparing traditional and modern construction methods. From all that, it produces real examples of contemporary construction efficiency, which can be seen in the construction of toll roads or bridges with advanced Technology, where technologies such as drones, IoT sensors, and BIM (Building Information Modeling)-based design software significantly increase work effectiveness. On the other hand, traditional construction is still used in remote areas or low-complexity projects that do not require advanced Technology. Therefore, choosing the right construction method must consider the scale of the project, its complexity, and the final goal to be achieved